A novel method to assess copy number variation in melanoma: Droplet digital PCR for precise quantitation of the RREB1 gene in formalin‐fixed, paraffin‐embedded melanocytic neoplasms, a proof‐of‐concept study. (22nd November 2022) - O'Hern, Keegan; Barney, Rachael; Chambers, Meagan; Baker, Catherine; Stevanovic, Mirjana; Tsongalis, Gregory J.; Hughes, Edward; Sriharan, Aravindhan
Abstract: Background: Melanocytic neoplasms can be challenging to diagnose. One well‐established diagnostic aid is the detection of copy number variation (CNV) in a few key genetic loci using conventional methods such as fluorescence in situ hybridization (FISH) and chromosomal microarray (CMA). Droplet digital polymerase chain reaction (ddPCR) is a novel, cost‐effective, rapid, and automated method to detect CNV. Methods: We perform the first investigation of ddPCR to assay Ras‐responsive element‐binding protein‐1 ( RREB1 ), the most common CNV in melanoma using formalin‐fixed, paraffin‐embedded (FFPE) melanocytic lesion samples; CMA data are used as the gold standard. Archival samples from 2013 to 2021 were analyzed, including 153 data points from 39 FFPE samples representing 34 patients. Benign, borderline, malignant, and metastatic melanocytic neoplasms were examined. Results: ddPCR showed a sensitivity and specificity of 93.8% and 95.7% using one reference gene, and 87.5% and 100% using a different reference gene for RREB1 gain detection. Conclusions: Here we show that ddPCR can provide inexpensive, rapid, and robust data on the commonest copy number alteration in melanoma. Future development and validation could provide a useful ancillary tool in the diagnosis of challenging melanocytic lesions.